Effect of a Probiotic Combination in an Experimental Mouse Model and Clinical Patients With Chronic Kidney Disease: A Pilot Study - Wang, I-Kuan; Yen, Tzung-Hai; Hsieh, Pei-Shan; Ho, Hsieh-Hsun; Kuo, Yi-Wei; Huang, Yen-Yu; Kuo, Yu-Lun; Li, Chi-Yuan; Lin, Hung-Chih; Wang, Jiu-Yao (Frontiers in Nutrition, 2021)
The aim of the present study was to evaluate whether probiotic administration could slow declining renal function. C57BL/6 mice (6–8 weeks of age, male) were fed a diet supplemented with adenine to induce chronic kidney disease (CKD). The experimental groups were additionally supplemented with 109 colony-forming units (CFU)/day (high-dose) and 107 CFU/day (low-dose) probiotics containing Lactobacillus acidophilus (TYCA06), Bifidobacterium longum subspecies infantis (BLI-02), and B. bifidum (VDD088). Renal function and histology were examined. Patients with stage 3–5 CKD and not on dialysis were recruited from July 2017 to January 2019. Two capsules of probiotics containing 2.5 × 109 CFU with the same composition were administered twice daily for 6 months. The decline in the estimated glomerular filtration rate (eGFR) was measured before and after the intervention. In addition, changes in the serum endotoxin and cytokine levels, gastrointestinal symptom scores, and the stool microbiota were measured. Probiotics could attenuate renal fibrosis and improve renal function in CKD mice. Thirty-eight patients completed the 6-month study. The mean baseline eGFR was 30.16 ± 16.52 ml/min/1.73 m2. The rate of decline in the eGFR was significantly slower, from −0.54 (−0.18, −0.91) to 0.00 (0.48, −0.36) ml/min/1.73 m2/month (P = 0.001) after 6 months of treatment. The serum levels of TNF-α, IL-6, IL-18, and endotoxin were significantly decreased after probiotic administration. Borborygmus and flatulence scores, as well as stool formation improved significantly. The abundance of B. bifidum and B. breve in the stool microbiota increased significantly. In conclusion, a combination of probiotics might attenuate renal function deterioration in CKD mice and human patients.